Clinical characteristics of petroclival meningioma and the impact of resection degree on its prognosis - Kang, Xi-peng; Fu, Jin; Qin, Jia-jun (Frontiers in Neurology, 2026)
BackgroundThe optimal surgical strategy for petroclival meningiomas (PCMs) remains debated, balancing the extent of resection against the risk of neurological morbidity. While the goal of gross total resection is widely acknowledged, its functional benefit is not uniform and may be significantly influenced by specific anatomical and pathological factors, such as cavernous sinus (CS) invasion patterns and World Health Organization (WHO) grade. This study aimed to develop and validate a quantitative, individualized surgical decision-making framework incorporating these understudied parameters.MethodsWe conducted a retrospective cohort analysis of 100 consecutive patients who underwent microsurgical resection for PCMs between 2013 and 2023. High-resolution MRI was used to preoperatively grade CS invasion (0–3 scale) and neurovascular encirclement (≥270° contact). Functional outcomes were assessed serially using the Karnofsky Performance Scale (KPS) preoperatively and up to 24 months postoperatively. Multivariable logistic regression and propensity score matching were employed to identify independent predictors of functional outcome (KPS improvement). Subgroup analyses informed the development of a novel Resection Utility Score (RUS).ResultsComplete resection predicted KPS improvement (OR = 2.34, p = 0.001), while CS invasion (OR = 0.52, p = 0.013), WHO Grade 2 (OR = 0.61, p = 0.022), and neurovascular encirclement (OR = 0.45, p = 0.002) reduced functional gains. The derived RUS guided a decision algorithm. For subgroups with RUS > 1 (CS 0–1, WHO Grade 1), complete resection was recommended. For RUS < 1 (CS 2–3, WHO Grade 2), subtotal resection was advised.ConclusionThe functional benefit of resection in PCMs is modulated by CS invasion and WHO grade. The proposed RUS and decision algorithm provide a quantitative, evidence-based framework for individualized surgical planning, shifting the paradigm from a universal goal of maximal resection toward a risk-adapted strategy aimed at optimizing functional preservation without compromising oncologic control. Prospective multicenter validation is warranted.